Defining the clinical phenotype of Saul-Wilson syndrome. - Ferreira, Carlos R. (Genet Med, 2020)
PURPOSE: Four patients with Saul-Wilson syndrome were reported between 1982 and 1994, but no additional individuals were described until 2018, when the molecular etiology of the disease was elucidated. Hence, the clinical phenotype of the disease remains poorly defined. We address this shortcoming by providing a detailed characterization of its phenotype. METHODS: Retrospective chart reviews were performed and primary radiographs assessed for all 14 individuals. Four individuals underwent detailed ophthalmologic examination by the same physician. Two individuals underwent gynecologic evaluation. Z-scores for height, weight, head circumference and BMI were calculated at different ages. RESULTS: All patients exhibited short stature, with sharp decline from the mean within the first months of life, and a final height Z-score between −4 and −8.5 standard deviations. The facial and radiographic features evolved over time. Intermittent neutropenia was frequently observed. Novel findings included elevation of liver transaminases, skeletal fragility, rod-cone dystrophy, and cystic macular changes. CONCLUSION: Saul-Wilson syndrome presents a remarkably uniform phenotype, and the comprehensive description of our cohort allows for improved understanding of the long-term morbidity of the condition, establishment of follow-up recommendations for affected individuals, and documentation of the natural history into adulthood for comparison with treated patients, when therapeutics become available.